2019
DOI: 10.3390/technologies7010023
|View full text |Cite
|
Sign up to set email alerts
|

Wet Relaxation of Electrospun Nanofiber Mats

Abstract: Electrospinning can be used to produce nanofiber mats. One of the often used polymers for electrospinning is polyacrylonitrile (PAN), especially for the production of carbon nanofibers, but also for a diverse number of other applications. For some of these applications—e.g., creation of nano-filters—the dimensional stability of the nanofiber mats is crucial. While relaxation processes—especially dry, wet and washing relaxation—are well-known and often investigated for knitted fabrics, the dimensional stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Detailed observation of the printing process if the nozzle is slightly too high suggests that the problem of missing adhesion for too large distances between nanofiber mat and printing nozzle may be based on electrostatic repulsion between the 3D printing polymer and the nanofiber mat. In a previous experiment, the electrostatic charging could be significantly reduced by soaking the nanofiber mat into water with a surfactant that was typically negatively charged [49]. Thus, 3D printing was also tested on a nanofiber mat that was soaked in soap water and dried in the air.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed observation of the printing process if the nozzle is slightly too high suggests that the problem of missing adhesion for too large distances between nanofiber mat and printing nozzle may be based on electrostatic repulsion between the 3D printing polymer and the nanofiber mat. In a previous experiment, the electrostatic charging could be significantly reduced by soaking the nanofiber mat into water with a surfactant that was typically negatively charged [49]. Thus, 3D printing was also tested on a nanofiber mat that was soaked in soap water and dried in the air.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, soaking and drying the sample in pure water or soap water before printing on it supports relaxation [49]. In this way, fixing it in a slightly stretched position was simpler than in case of not watered samples, in order to ensure that no elongation of the specimen was possible due to thermal and mechanical impact during printing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from their many advantages, the weak mechanical properties of nanofibers restrict their use in a wider variety of applications. Grothe et al [17] found that the dimensional stability of nanofibers changes in wet applications. Attempts have been made to improve the mechanical weakness of nanofibers, including polymer blending [18], inorganic blending [19], the use of epoxy composites [20], thermal lamination [21], dip-coating [22], and ultrasonic welding [23].…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent decades have seen much attention paid to the effect of the textile manufacturing process and domestic garment laundering on fabric dimensional stability. [6][7][8][9][10][11][12][13][14][15][16][17] During these processes, fabric dimensional properties are largely affected by moisture content and temperature. Attention has also been extended from wool [6][7][8] to other textile materials, such as cotton, [9][10][11] linen, 12 silk 13 and polyester.…”
mentioning
confidence: 99%